El ejemplar de la Biblioteca Pública "Fernando de Loazes" de Orihuela del De conscribendis epistolis de Francisco J. Bardaxí: ¿una edición corregida por el autor? - Arcos Pereira, Trinidad (Fortunatae: Revista canaria de Filología, Cultura y Humanidades Clásicas, 1999)
In this paper we analyse the differences between the two surviving copies of Francisco Juan Bardaxí's De conscribendis epistolis kept in the Biblioteca Nacional in Madrid and in the Biblioteca Pública «Fernando de Loazes» in Orihuela respectively. From the differences between the texts of both copies we can conclude (a) that the autor corrected the text during the printing process; (b) that these corrections are preserved only in the copy of Orihuela and (c) therefore, an edition of this work should be based on the copy in Orihuela.